2009
DOI: 10.1002/hyp.7494
|View full text |Cite
|
Sign up to set email alerts
|

Development of design flood hydrographs using probability density functions

Abstract: Abstract:Probability density functions (PDFs) are used to fit the shape of hydrographs and have been popularly used for the development of synthetic unit hydrographs by many hydrologists. Nevertheless, modelling the shapes of continuous stream flow hydrographs, which are probabilistic in nature, is rare. In the present study, a novel approach was followed to model the shape of stream flow hydrographs using PDF and subsequently to develop design flood hydrographs for various return periods. Four continuous PDFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 18 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Hydrologic forcing is estimated using a rainfall-runoff model that quantifies flood peak discharges or a flow hydrograph for a given return period (T) [6,[11][12][13]. The hydraulic analysis can been performed using an Event Based Approach (EBA) [14,15], a Semi-Continuous Approach (SCA) [11][12][13], and a Fully Continuous Approach (FCA) [6]. The analysis is carried out using a one-dimensional (1D) surface water model or two-dimensional (2D) flood routing algorithm to simulate the spatially distribution of flow and velocity dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrologic forcing is estimated using a rainfall-runoff model that quantifies flood peak discharges or a flow hydrograph for a given return period (T) [6,[11][12][13]. The hydraulic analysis can been performed using an Event Based Approach (EBA) [14,15], a Semi-Continuous Approach (SCA) [11][12][13], and a Fully Continuous Approach (FCA) [6]. The analysis is carried out using a one-dimensional (1D) surface water model or two-dimensional (2D) flood routing algorithm to simulate the spatially distribution of flow and velocity dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…A greater number of g(t) functions is likely to be required for more complex hydrographs. A similar set of different inverse Gaussian distributions would have served equally well, as could other distributions discussed by various authors (Nadarajah, 2007;Pramanik et al, 2010;Muneepeerakul et al, 2010).…”
Section: Example Applicationmentioning
confidence: 74%
“…We assess pre-fire model performance for both calibrated and uncalibrated models using flood frequency information from gaged watersheds. The Weibull method is commonly used to analyze streamflow and estimate expected frequency of flows based on the assumption that peak discharge is evenly distributed over a long period of time (Pramanik et al, 2010). The generated discharge values for each recurrence event are considered a reasonable approximation of the associated probability density of discharge values in a basin and allow comparison of modeled design storm simulations to an "observed" storm frequency (Clarke, 2002;Pramanik et al, 2010).…”
Section: Model Calibrationmentioning
confidence: 99%
“…The Weibull method is commonly used to analyze streamflow and estimate expected frequency of flows based on the assumption that peak discharge is evenly distributed over a long period of time (Pramanik et al, 2010). The generated discharge values for each recurrence event are considered a reasonable approximation of the associated probability density of discharge values in a basin and allow comparison of modeled design storm simulations to an "observed" storm frequency (Clarke, 2002;Pramanik et al, 2010). In the current study, a Weibull frequency distribution is generated using the observed peak flow values for basins where long-term peak discharge exists (Andrews Creek To evaluate performance, we utilize two commonly used metrics, root mean square error (RMSE), and percent bias:…”
Section: Model Calibrationmentioning
confidence: 99%